IMPLEMENTASI MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN KOMPETENSI BILANGAN 1–10 PADA SISWA KELAS I SD - Aripin, Fajar Yumanhadi; Ikrom, Fadhli Dzil (LPPM Universitas Bina Bangsa, 2025)
This study aims to examine the effectiveness of implementing the discovery learning model integrated with the scientific approach in improving number competency (1–10) among first-grade elementary school students. The background of the study is rooted in the low conceptual understanding of numbers due to the use of conventional teaching methods that are not aligned with the cognitive development stages of young learners. Using the STAR method (Situation, Task, Action, Result), the research was conducted at SDN Gandaria I with 25 first-grade students as participants. The learning process was designed with exploratory activities using concrete media and differentiated instructional strategies. The results show significant improvements in conceptual understanding, scientific process skills, learning motivation, mathematical communication, and problem-solving abilities. This learning model has proven effective in building a strong and enjoyable mathematical foundation from an early age. The study recommends the application of similar strategies for other math competencies at the lower elementary level.